A certain class of harmonic mappings related to functions of bounded radius rotation - Kahramaner, Yasemin; Yemişçi Şen, Arzu; POLATOĞLU, YAŞAR (My University, 2018)
Let R-k be the class of functions with bounded radius rotation and let S-H be the class of sense-preserving harmonic mappings. In the present paper we investigate a certain class of harmonic mappings related to the function of bounded radius rotation.
Keywords: Harmonic Mapping; Bounded Radius Rotation; Distortion Theorem; Growth Theorem and Radius of Starlikeness